Causes, Effects and Consequences of Cultural Differences: Reading Nepali Migrants' Literature in West Asia - Timalsina, Ramji (JODEM: Journal of Language and Literature, 2020)
This exploratory study deals with the depiction of causes, effects and consequences of cultural differences between the Nepali transnational migrants in West Asia and the citizens of the nations in this locale as seen in the literary creations of Nepali migrant writers. About a million Nepali migrants work in the Middle East. In the three decades of this migration, they have undergone many experiences of awe and shock caused by their cultural differences with the host land societies. Mainly caused by the differences in terms of religion, social management and law, the Nepali migrants feel difficult to adjust in the respective societies and they bear the consequent discomforts. These experiences have been the base of the Nepali literary creations in that transnational locale. The authors have expressed these realities in their poems, novels, stories, essays and memoirs. This article shows how these writings have portrayed the impact of closed Islamic society unlike the open society in Nepal; occupation based social hierarchy unlike the caste based one in Nepal; differences in culinary items and chance of personal freedom; distance between male and female; the traditional concept about the housemaids and workers; and other socio-cultural discriminations on the migrants in West Asia. The texts under analysis show that whatever is the social background back in Nepal, all Nepali migrants have the same culture, i.e. Nepali; and so they try to save it for their solace in the hostland.